Characterization of a Mycobacterium avium subsp. avium Operon Associated with Virulence and Drug Detoxification - Viale, Mariana Noelia (2014)
The lprG-p55 operon of Mycobacterium tuberculosis and Mycobacterium bovis is involved in the transport of toxic compounds. P55 is an efflux pump that provides resistance to several drugs, while LprG is a lipoprotein that modulates the host's immune response against mycobacteria. The knockout mutation of this operon severely reduces the replication of both mycobacterial species during infection in mice and increases susceptibility to toxic compounds. In order to gain insight into the function of LprG in the Mycobacterium avium complex, in this study, we assayed the effect of the deletion of lprG gene in the D4ER strain of Mycobacterium avium subsp. avium. The replacement of lprG gene with a hygromycin cassette caused a polar effect on the expression of p55. Also, a twofold decrease in ethidium bromide susceptibility was observed and the resistance to the antibiotics rifampicin, amikacin, linezolid, and rifabutin was impaired in the mutant strain. In addition, the mutation decreased the virulence of the bacteria in macrophages in vitro and in a mice model in vivo. These findings clearly indicate that functional LprG and P55 are necessary for the correct transport of toxic compounds and for the survival of MAA in vitro and in vivo.